Serum miR-222-3p as a Double-Edged Sword in Predicting Efficacy and Trastuzumab-Induced Cardiotoxicity for HER2-Positive Breast Cancer Patients Receiving Neoadjuvant Target Therapy - Zhang, Shan; Wang, Yaohui; Wang, Yan; Peng, Jing; Yuan, Chenwei; Zhou, Liheng; Xu, Shuguang; Lin, Yanping; Du, Yueyao; Yang, Fan; Zhang, Jie; Dai, Huijuan; et al. (Frontiers in Oncology, 2020)
Background: We aimed to explore whether the expression of serum miR-222-3p might contribute to early prediction of therapeutic response, clinical outcomes, and adverse events for HER2-positive breast cancer patients receiving neoadjuvant therapy (NAT). Methods: A total of 65 HER2-positive breast cancer patients receiving NAT were analyzed. The concentration of serum miR-222-3p was detected by quantitative real-time PCR. Logistic regression analysis was used to identify the association of serum miR-222-3p with pathological complete response (pCR). The relationship of serum miR-222-3p with disease-free survival (DFS) and overall survival (OS) was examined via log-rank test and Cox proportional hazards analysis. The ordered logistic regression was applied to evaluate the association between serum miR-222-3p and adverse events. Results: The miR-222-3p low group was more likely to achieve pCR [odds ratio (OR) = 0.258, P = 0.043]. The interaction between miR-222-3p and presenting Ki67 level was also detected for pCR (OR = 49.230, Pinteraction = 0.025). The miR-222-3p low group was correlated with superior DFS (P = 0.029) and OS (P = 0.0037). The expression of serum miR-222-3p was the independent protective factor for trastuzumab-induced cardiotoxicity (P < 0.05) and anemia (P = 0.013). Conclusions: Serum miR-222-3p is the potential factor to predict pCR, survival benefit and trastuzumab-induced cardiotoxicity for HER2-positive breast cancer patients receiving NAT.